Isolation, partial purification and identification of Pregnancy-Specific Protein B (PSPB) in Kedah-Kelantan cattle using placenta cotyledon - Muhammad Aiman Adam (2023)
Early and accurate pregnancy detection is important for improving breeding management to increase beef production and shorten the breeding interval for Kedah Kelantan (KK) cattle in Malaysia. Pregnancy-Specific Protein B (PSPB) has been utilised as a pregnancy marker for monitoring ruminant pregnancy. Therefore, the present study aims to isolate, partial purify and identify PSPB using KK placenta cotyledons. The cotyledon tissues underwent freeze-drying prior to protein extraction. Extraction included the use of radioimmunoprecipitation assay buffer (RIPA buffer), pH 7.6, supplemented with protease inhibitor cocktail (Pi), and centrifuged. Extracted samples were initially precipitated with 40% ammonium sulfate saturation and further precipitated with higher ammonium sulfate saturation (40-65,40-70, 40-75 and 40- 80%). Bradford assay was used for total protein and Enzyme-link immunosorbent assay (ELISA) for total PSPB quantification. The 40% ammonium sulfate samples were further purified by gel filtration chromatography (GFC) on Sephadex G-75. One-dimensional Sodium Dodecyl Sulfate-Polyacrylamide Gel Electrophoresis (1D SDS-PAGE) was performed to determine the PSPB molecular weight (MW). Selected 40-80% ammonium sulfate bands were subjected to peptide identification by electrospray ionisation mass spectrometry. Results showed that total protein and protein recovery decreased after precipitation at 40% saturation (7.89 ± 0.00 mg, 49.78 ± 2.13%). 40-80% ammonium sulfate saturation showed a significant difference compared to 40-70 and 40-75% saturations due to a higher loss of total protein yield and recovery. Concurrently, the recovery and total PSPB in 40% ammonium sulfate displayed a decrease. However, the ratio between total PSPB and total protein and purification fold (0.000932,1.20±0.05) appeared to increase. On the other hand, total PSPB and recovery appeared to decrease further in the second stage precipitation, resulting in irreversible protein denaturation. Based on gel electrophoresis, the MW of bovine PSPB (bPSPB) was expressed at 64.26 and 56.99 kDa. After performing electrospray ionisation mass spectrometry, selected bands of 40-80% saturation could not identify PSPB. However, Alpha-fetoprotein expression associated with PAG/PSPB identification of pregnancy-associated glycoprotein (PAG) was consistent with previous studies. In conclusion, the isolation of a biomarker of bPSPB from KK freeze-dried cotyledon tissues is possible via 40-80% precipitation and it is suggested that this could be a valuable indicator for early and accurate pregnancy detection.